2015
DOI: 10.1007/s00467-015-3178-3
|View full text |Cite
|
Sign up to set email alerts
|

Urinary KIM-1 in children undergoing nephrotoxic antineoplastic treatment: a prospective cohort study

Abstract: Background Acute kidney injury (AKI) is a significant complication in patients with cancer, and nephrotoxic drugs are among the most common causes of AKI. To date, there is no study evaluating the potential role of renal biomarkers in children receiving nephrotoxic chemotherapy. Methods A prospective study was conducted in children receiving methotrexate (MTX) or platinum-based treatment. Urinary kidney injury molecule-1 (KIM-1) was measured 24 h after the initiation of the chemotherapy infusion, and serum cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…They reported the increase of KIM‐1 in renal tissue and an augmented urinary NAG and Cys C . On the other hand, Carvalho Pedrosa et al showed a direct correlation between MTX serum levels and urinary KIM‐1 levels 24 hours after MTX infusion in paediatric patients. In the same way, plasma Cys C was useful to evaluate the renal performance before and after the infusion of HDMTX in paediatric patients with acute lymphoblastic leukaemia .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They reported the increase of KIM‐1 in renal tissue and an augmented urinary NAG and Cys C . On the other hand, Carvalho Pedrosa et al showed a direct correlation between MTX serum levels and urinary KIM‐1 levels 24 hours after MTX infusion in paediatric patients. In the same way, plasma Cys C was useful to evaluate the renal performance before and after the infusion of HDMTX in paediatric patients with acute lymphoblastic leukaemia .…”
Section: Discussionmentioning
confidence: 98%
“…After different MTX treatments in rats, some studies employed novel biomarkers to assess renal damage, besides measuring the traditional ones (such as blood urea nitrogen and plasma creatinine). They reported the increase of KIM-1 in renal tissue 30,31 and an augmented urinary NAG 32 and Cys C. 33 On the other hand, Carvalho Pedrosa et al 34 showed a direct correlation between MTX serum levels and urinary KIM-1 levels 24 hours after MTX infusion in paediatric patients. In the same way, plasma Cys C was useful to evaluate the renal performance before and after the infusion of HDMTX in paediatric patients with acute lymphoblastic leukaemia.…”
Section: Discussionmentioning
confidence: 98%
“…Few studies (almost only in adults) evaluated AKI biomarkers in chemotherapy AKI . In Cis‐treated adults, AKI biomarker concentrations were elevated before treatment .…”
Section: Discussionmentioning
confidence: 99%
“…34 Kidney injury molecule 1 is also a useful marker of kidney function in children undergoing chemotherapy with MTX or cisplatin derivatives. 35 Although the value of KIM-1 as a marker for AKI has been demonstrated in a recent meta-analysis, 36 none of the data concerned the detection of AKI following HSCT.…”
Section: Kidney Injury Moleculementioning
confidence: 99%